AB0209 Endothelin-1 Induces Direct Activation of JNK and C-Jun Signalling Pathways in Cultured Human Dermal Fibroblasts. (10th June 2014) - Soldano, S.; Brizzolara, R.; Montagna, P.; Sulli, A.; Gianetta, E.; Cutolo, M.
Abstract : Background: Myofibroblasts are final key mediators of the fibrotic process in several autoimmune connective tissue diseases, including systemic sclerosis (SSc) and contribute to the excessive synthesis and deposition of extracellular matrix (ECM) molecules (i.e. fibrillar collagens, fibronectin) in skin and internal organs (1-3). Several growth factors, such as transforming growth factorβ (TGFβ), induce myofibroblast differentiation through the activation of intracellular signalling pathways, as Jun-N-terminal kinase (JNK) or c-Jun (4). Endothelin-1 (ET-1) plays an important role in SSc, inducing the activation of myofibroblasts to enhance the synthesis of ECM proteins (5, 6). Objectives: To investigate the ability of ET-1 to directly induce the activation of the intracellular signalling pathways involved in the profibrotic myofibroblast activation in cultured human normal dermal fibroblasts. Methods: Cultured human dermal fibroblasts were obtained from skin biopsies of four healthy subjects (mean age 65±12 years) during diagnostic procedures and after signing informed consent. After serum starvation (18 hrs), cultured human dermal fibroblasts at 3rd culture passage were treated with ET-1 (100nM) for 30 minutes, 1 hr and 6 hrs, in accordance with recent studies (6, 7). Untreated cells were used as controls. The myofibroblast phenotype activation was investigated by immunofluorescence (IF) evaluating the α-smooth muscle actin (α-SMA) expression. The activation of JNK, c-Jun, protein kinase B (Akt) and mitogen activated protein kinase (MAPK) Erk1/2 were investigated by Western blotting, evaluating the phospho-JNK, phospho-c-Jun, phospho-Akt and phospho-Erk1/2 and their non-activated proteins. Results: ET-1 was able to induce α-SMA expression in cultured human dermal fibroblasts confirming their activation into myofibroblasts. Interestingly, ET-1 directly induced the activation of both JNK and c-Jun through their phosphorylation after 30 minutes of treatment and this effect increased after 1 hrs and 6 hrs of treatment with ET-1 in cultured human dermal fibroblasts. Moreover, ET-1 was able to induce the phosphorylation of both Erk1/2 and Akt in these cultured cells confirming the results observed in cultured human lung fibroblasts (7). Conclusions: These observations might support a possible direct action of ET-1 in activating important intracellular signalling pathways, primarily JNK/c-Jun, which have been observed to contribute to the persistence of the myofibroblast phenotype that characterize the fibrotic process in several autoimmune connective tissue diseases, including SSc (1, 7). References: Bhattacharyya S et al. Nat Rev Rheumatol 2012;8:42-51. Wynn TA et al. Nat Rev 2012;18:1028-40 Wej J et al. Autoimmun Rev. 2011;10:267-75. Fibrogenesis Tissue Repair. 2010 May 27;3:8 (doi: 10.1186/1755-1536-3-8). Soldano S et al. Reumatismo. 2012;64:326-34. Shi-wen X et al. Arthrit Rheum 2007;56:4189-94. Shi-wen X et al. Mol cell Biol 2006;26:5518-26. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6009